Exploring the impact of lithium halide-based redox mediators in suppressing CO2 evolution in Li-O2 cells - Akella, Sri Harsha; Bagavathi, Muniyandi; Rosy, None; Sharon, Daniel; Ozgur, Capraz; Noked, Malachi (Royal Society of Chemistry, 2023)
The realization of lithium-oxygen (Li-O2) batteries has been impeded by parasitic reactions that cause cell component degradation, often accompanied by the release of CO2 gas during oxidation reactions. The use of halide-based redox mediators (RMs) like LiBr and LiI has been proposed as a strategy to reduce overpotentials during oxygen evolution reactions and thus suppress the subsequent evolution of CO2. However, there is a scarcity of research examining the effectiveness of these RMs in the direct mitigation of parasitic reactions. In this study, we investigated the evolution of CO2 during the oxidation processes using an online electrochemical mass spectrometer. The results show that cells without RMs exhibited high overpotentials and significant CO2 evolution from the first charging cycle. In contrast, the addition of 50 mM LiI to the electrolyte resulted in a delay in CO2 evolution, observed only after several cycles. Notably, no CO2 evolution was observed in cells containing 50 mM LiBr in 0.5 M LiTFSI during the cell cycling. Our findings demonstrate that while the mechanism of halide-based RMs may be similar, their chemical properties and electrochemical behaviour can greatly influence their ability to effectively mediate the oxygen evolution process.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Bromine compounds; Cells; Cytology; Electrolytes; Lithium compounds; Lithium-air batteries; Oxygen; Redox reactions